2020
DOI: 10.1093/schbul/sbaa060
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Combination and Augmentation Strategies in Patients With Schizophrenia —Recommendations From an International Expert Survey Among the Treatment Response and Resistance in Psychosis (TRRIP) Working Group

Abstract: Background Evidence for the management of inadequate clinical response to clozapine in treatment-resistant schizophrenia is sparse. Accordingly, an international initiative was undertaken with the aim of developing consensus recommendations for treatment strategies for clozapine-refractory patients with schizophrenia. Methods We conducted an online survey among members of the Treatment Response and Resistance in Psychosis (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 38 publications
3
81
0
Order By: Relevance
“…Previous studies have suggested that clozapine blood concentrations ≥350 ng/mL are associated with superior symptomatic outcome. 26 However, determining the required dose for an individual to achieve this target blood concentration and symptomatic relief can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that clozapine blood concentrations ≥350 ng/mL are associated with superior symptomatic outcome. 26 However, determining the required dose for an individual to achieve this target blood concentration and symptomatic relief can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, higher clozapine doses, concentrations, and treatment durations were reported in responders as compared to non-responders [ 32 ]. Furthermore, waiting for a delayed clozapine response for persistent positive symptoms was recommended over plasma level-guided dose escalation in the recent consensus recommendations by the TRRIP working group [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent multicenter investigation with long follow-up, clozapine augmentation with the atypical antipsychotic, paliperidone, has shown significant relief of symptoms, lower number of hospitalization, and improved functionality [ 40 ]. Finally, a consensus of treatment strategies for refractory schizophrenia patients was introduced by the TRRIP working group, where combinations of clozapine and atypical antipsychotics such as aripiprazole or amisulpride were recommended for refractory positive and mixed symptoms [ 33 ], in line with the current study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Clozapine monotherapy is considered by most guidelines and expert consensus the most effective medication for TRS [27][28][29][30]. However, only 40% of people will meet response criteria, being necessary to establish well evidenced-bases clozapine augmentation strategies [31][32][33]. Recent systematic meta-review of available evidence and international expert consensus point that augmentation with second-generation antipsychotics and firstgeneration antipsychotics can be beneficial, but the supporting evidence is from low-quality studies [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…However, only 40% of people will meet response criteria, being necessary to establish well evidenced-bases clozapine augmentation strategies [31][32][33]. Recent systematic meta-review of available evidence and international expert consensus point that augmentation with second-generation antipsychotics and firstgeneration antipsychotics can be beneficial, but the supporting evidence is from low-quality studies [32,33]. A previous retrospective 1-year mirror-image study reported that clozapine and various LAI antipsychotics (mainly first generation and risperidone) combination was beneficial and safe in a cohort of 17 multi-episode patients diagnosed with schizophrenia and schizoaffective disorder [3].…”
Section: Introductionmentioning
confidence: 99%